2007
DOI: 10.1007/s10021-007-9095-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spatial Legacies following Shifting Management Practices and Fire on Boreal Forest Age Structure

Abstract: Forest age structure and its spatial arrangement are important elements of sustainable forestry because of their effects on biodiversity and timber availability. Forest management objectives that include specific forest age structure may not be easily attained due to constraints imposed by the legacies of historical management and natural disturbance. We used a spatially explicit stochastic model to explore the synergetic effects of forest management and fire on boreal forest age structure. Specifically, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Spatial-genetic structure within populations is likely less dependent on the resistance of the landscape matrix (Fahrig 2007), but more strongly influenced by many other biological and ecological factors acting locally, including sex-specific space-use behavior, local population density, survival, or reproductive success (Pflü ger and Balkenhol 2014). Another issue related to genetic data is that in long-lived species there may be a temporal disconnection between genetic structure and the current landscape; i.e., there may be legacy effects of previous landscapes (James et al 2007, Spear et al 2010) that could lead to misestimate current connectivity. However, Landguth et al (2010) showed that the legacy of past landscape features is not a particularly important problem in species with relatively large dispersal abilities.…”
Section: Genetic Data Estimate Higher Resistance To Movement Through mentioning
confidence: 99%
“…Spatial-genetic structure within populations is likely less dependent on the resistance of the landscape matrix (Fahrig 2007), but more strongly influenced by many other biological and ecological factors acting locally, including sex-specific space-use behavior, local population density, survival, or reproductive success (Pflü ger and Balkenhol 2014). Another issue related to genetic data is that in long-lived species there may be a temporal disconnection between genetic structure and the current landscape; i.e., there may be legacy effects of previous landscapes (James et al 2007, Spear et al 2010) that could lead to misestimate current connectivity. However, Landguth et al (2010) showed that the legacy of past landscape features is not a particularly important problem in species with relatively large dispersal abilities.…”
Section: Genetic Data Estimate Higher Resistance To Movement Through mentioning
confidence: 99%
“…Past abiotic events, spatial configuration and species assemblages are known to constrain subsequent ecological processes (known as legacy effects; Peterson 2002, James et al 2007, Cuddington 2012.…”
Section: Legacy Effectsmentioning
confidence: 99%
“…Even though it is more time-consuming than newer approaches, aerial photo interpretation is a good compromise between costs and precision, particularly when working at fine scales. As a consequence, it is currently widely employed by governmental agencies and forest managers (James et al, 2007).…”
Section: Aerial Photo Interpretationmentioning
confidence: 99%